Additive effects of temperature and infection with an acanthocephalan parasite on the shredding activity of Gammarus fossarum (Crustacea Amphipoda): the importance of aggregative behavior - Labaude, Sophie (Global change biology, 2017)
© 2016 John Wiley & Sons Ltd.